STEAM Education Based On Local Wisdom Of Coffee Plantation In Jember To Improve The Competitiveness at 21st Century - Samsul Bahri; Linda Kusumawati; Lailatul Nuraini (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
In the 21st century, an educational institution needs to consider coverage graduates that success is not confined to academic ability, but more to the abilities and skills that will help graduates to compete in a global and digital world today. An important skill to have in the digital age, such as critical thinking skills, problem-solving, creativity, ability to communicate and collaborate as well as having the ability in information technology.This study conducted to describe the learning outcome and response of students with the use of science teaching material that integrated STEAM education and based on Jember’s local wisdom. The design of development by using a model of ADDIE (Analysis, Design, Develop, Implement and Evaluate). This research has done in MTs. Bustanul Ulum, Jember in class VII A with 25 sample. The results of the validation average of 4.31 by experts 1, and 4.09 by experts 2. The results of students’ cognitive and psychomotor are 73.84 and 91.8. The average score of student’s response is 0.91. It means the teaching materials that developed is very valid, the value of the cognitive is good enough, the psychomotor is very high and the given of response is very positive, so the teaching materials are feasible to implement and this teaching materials can improved performance and student’s motivation to learn.